2-D wireless human subjects positioning system based on respiration detections - Yu-Sheng Su; Chia-Chan Chang; Jhe-Jyun Guo; Sheng-Fuh Chang (2012 IEEE/MTT-S International Microwave Symposium Digest, 2012)
A tag-free 2-D wireless positioning system for human subject tracking is proposed in this paper. Two techniques are integrated in this system. A quadrature Doppler radar is developed to sense the presence of human subject upon the respiration signal detection, while the switched-beam phased antenna array is utilized to determine the target's angular information. With two radars employed, the 2-D positioning can be achieved based on angle of arrival (AoA) algorithm. Experiments by 2.28-GHz switched-beam radar systems have been performed to verify these two techniques.